Benchmarking Sustainable Construction Technology - Beheiry, Salwa (2011)
The objective of this research was to measure the use of recognized technology that promotes and supports sustainable development in building construction projects. This research hinged on the use of the Sustainable Construction Technology Index (SCTI) developed by Beheiry and Abu-Lebdeh in 2009 [1]. The SCTI was created in 2009 to investigate the use of technology in all phases of the building process from planning to occupancy. The index consists of four main sections that address the major phases of a typical construction project. These phases include the planning phase, the design phase, the construction phase and the occupancy phase. In the first stage of the research the SCTI was validated using expert feedback and weighted using trial data samples of close to 100 projects. In this stage of the research the SCTI was used to collect data from 208 building construction projects executed between 2005 and 2010 in the United Arab Emirates (UAE). The study brings to light that low and renewable energy use systems are spearheading the change process to more sustainable technologies in building construction projects in the UAE, followed by water preservation and reuse systems. The study also shows that the use of sustainable technology is still relatively low in residential buildings, compared to newer commercial buildings. The data show a clear trend upwards in the use of the technology albeit the total use is still low. This research provided a benchmark for current sustainable technology use in UAE project and a platform for further sustainable construction planning.